Easy access to oxygenated block polymers via switchable catalysis - Stößer, T; Sulley, G; Gregory, G; Williams, C (Springer Nature, 2019)
Oxygenated block polyols are versatile, potentially bio-based and/or degradable materials widely applied in the manufacture of coatings, resins, polyurethanes and other products. Typical preparations involve multistep syntheses and/or macroinitiator approaches. Here, a straightforward and well-controlled one-pot synthesis of ABA triblocks, namely poly(ether-b-ester-b-ether), and ABCBA pentablocks, of the form poly(ester-b-ether-b-ester'-b-ether-b-ester), using a commercial chromium catalyst system is described. The polymerization catalysis exploits mechanistic switches between anhydride/epoxide ring-opening copolymerization, epoxide ring-opening polymerization and lactone ring-opening polymerization without requiring any external stimuli. Testing a range of anhydrides, epoxides and chain-transfer agents reveals some of the requirements and guidelines for successful catalysis. Following these rules of switch catalysis with multiple monomer additions allows the preparation of multiblock polymers of the form (ABA)n up to 15 blocks. Overall, this switchable catalysis delivers polyols in a straightforward and highly controlled manner. As proof of potential for the materials, methods to post-functionalize and/or couple the polyols to make higher polymers are demonstrated.